Kids detector system via radio frequency identification (RFID) / Mohammad Aizat Noor Azman - Noor Azman, Mohammad Aizat (2009)
This paper will discuss about how to create a system or device that can help teacher or caretaker in monitoring their kids at the kindergarten using the RFID technology. The system is operates by warn the caretaker in term of sound if the kids or a person who have been attach with the tag, over the radiation pattern of the antenna of the reader. Visual Basic. Net was used to process all the data received from the reader and show the output based on the data recieved. This system use Graphical User Interface to create an icons to help the user, so that the system can be used easily. Finally the strength of the RF signal was measured to determine how far the antenna of the reader can transmit the RF signal and to determine if there is any different in term of strength when the tag is at different locations.